The Role of Political Connections in Moderating Profitability, Leverage, and Institutional Ownership on Firm Value: Empirical Evidence from the Indonesian Banking Industry - Mustarudin; Wendy; Yuli; Azazi, Anwar; Syahputri, Anggraini (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of political connections, profitability, and leverage on firm value in banking companies listed on the Indonesia Stock Exchange for the period 2019–2024, with institutional ownership acting as a moderating variable. The research sample consisted of 39 companies with a total of 234 observations selected through purposive sampling, using secondary data sourced from financial reports and share ownership information. The analysis was conducted using Moderated Regression Analysis (MRA) based on panel data. The results show that internal company determinants have an impact on firm value with varying intensity, while political connections are proven to play a selective role in moderating this relationship. These findings contribute to enriching the literature on firm value determinants in the banking sector and governance implications in a highly regulated industry.